1999
DOI: 10.1103/physreva.60.2047
|View full text |Cite
|
Sign up to set email alerts
|

Valence-hole localization in core-valence doubly ionized states of ionic molecules and its impact onKLVAuger spectroscopy

Abstract: The complete spectra of core-valence dicationic states, i.e., states with one vacancy in the core and one in the valence shell, of the molecules BF 3 , AlF 3 , BCl 3 , and AlCl 3 , are investigated by the Green's-function method. An analysis of the double-hole density in the corresponding correlated states shows that when the core hole is on a ligand ͑halogen͒ atom, the valence hole is also strongly localized, either on the same ligand or on a different ligand. As a result these states can be classified as eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…However, the early ADC(4) results could be greatly compromised by the introduced CVS approximation, which made the computation of eigenstates deeply embedded in the large ADC secular matrix possible, but neglected some weak core−valence couplings that could lead to non-negligible satellites in the spectrum. For example, in an early ADC(2) study of the F 1s dicationic states of BF 3 molecule, 114 it was found that both 3 A 1 and 1 A 1 main peaks passed some weight to accompanying satellites, whereas only the 3 A 1 did it when incorporating the method with the CVS approximation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, the early ADC(4) results could be greatly compromised by the introduced CVS approximation, which made the computation of eigenstates deeply embedded in the large ADC secular matrix possible, but neglected some weak core−valence couplings that could lead to non-negligible satellites in the spectrum. For example, in an early ADC(2) study of the F 1s dicationic states of BF 3 molecule, 114 it was found that both 3 A 1 and 1 A 1 main peaks passed some weight to accompanying satellites, whereas only the 3 A 1 did it when incorporating the method with the CVS approximation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Core-valence doubly ionized states of molecules, which have holes in one core and one valence orbitals, are peculiar dication electronic states, considering the localized and relatively delocalized (or partially localized) characters of the two holes [1,2]. Only recently has spectroscopic investigation of these molecular doubly ionized states taken up, thanks to the development of electron coincidence methods.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we present the first observation of corevalence doubly ionized states of OCS, using the threshold photoelectron-Auger electron coincidence technique. The electronic configuration of OCS in its ground state can be written as (6σ ) 2 (7σ ) 2 for the inner valence orbitals and (8σ ) 2 (9σ ) 2 (2π) 4 (3π) 4 (4π) 0 (10σ ) 0 for the outer valence orbitals. Here, the 9σ and 3π valence orbitals have large S 3p contribution, while 8σ and 2π are localized on the CO side [10].…”
Section: Introductionmentioning
confidence: 99%
“…At somewhat higher energy transfers, collisions can create initial states with a core vacancy and simultaneous ejection of a valence electron; these are called core-valence states (see, for instance, Refs. [13][14][15][16] and references therein) or shake-off states and their energies and decay processes are hitherto unknown. At even higher energies it becomes possible to create a double vacancy in the core, that is, in the present context, a hollow molecule with no electrons left in the 1s orbital [17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%